Effect of screw - worm fly, Chrysomya bezziana larvae in cattle and treatment - Barhoom, Salameh Sh.; Kadhim, F. Sh. (The Iraqi Journal of Veterinary Medicine, 1999)
Field study on the effect of screw - worm fiy Chrysomya bezziana_larvae in 216 cattle and efficacy of different drugs used for the treatment was conducted. The clinical findings were : anoraxia , irritation, congestion of penis , lameness, decrease of milk production and lose of body weight. The distribution of myiasis on various body parts observed was: 111 (51.4%); perineal area , 24 (11%), head, 7(3.4%), udder , 6(2.8%), nave!, 1(0.4%), testes , 4(1.89), tail, 3(1.4%), legs and 60 (28.2%) penis The activity of diazinone, coumaphos , cypermethlin and vermectin by administration the drug subcutaneously at a dose rate 0.2 mg/kg body weight against naturally infesting wounds with screw - Worm fly larvae in cattle have been tested. The results showed emerges of the larvae outside the infested wound after treatment with cypermethlin and diazinone while coumaphos kill the larvae . Ivermectin kill the larvae after 24 hours.